Liouville property and existence of entire solutions of Hessian equations. (October 2022) - Wang, Cong; Bao, Jiguang
Abstract: In this paper, we establish the existence and uniqueness theorem for entire solutions of Hessian equations with prescribed asymptotic behavior at infinity. This extends the previous results on Monge–Ampère equations. Our approach also makes the prescribed asymptotic order optimal within the range preset in exterior Dirichlet problems. In addition, we show a Liouville type result for k -convex solutions. This partly removes the ( k + 1 ) - or n -convexity restriction imposed in existing work.